PENGUATAN EKONOMI PEREMPUAN DESA MELALUI PELATIHAN INOVASI OLAHAN PRODUK KREATIF BERBASIS POTENSI LOKAL PERIKANAN DAN PERTANIAN DI DESA BUATA, BOTUPINGGE, BONE BOLANGO - Mile, Lukman; Nento, Wila Rumina; Djailani, Fernandy M.; Sumrin, Sumrin; Manteu, Shindy Hamidah (Jurnal Abdi Insani, 2025)
The main objective of this program is to enhance the economic independence and welfare of women in Buata Village through the utilization of existing local potential, particularly in the fields of fisheries and agriculture. The method used involves several aspects observed through field observation, including social, economic, employment, participation, and community empowerment aspects. The outcome of the program includes the development of a processed product Jantung Pisang Sambal Goreng (JAPOSANG) which introduces and strengthens the identity of Buata Village's local products through branding initiatives. This program supports local entrepreneurs, especially housewives, in developing their businesses more professionally. With branding, the product becomes more recognizable, competitive, and has the potential to enter broader markets. Moreover, through branding training and mentoring, the community gains new insights into the importance of modern marketing, packaging techniques, and simple promotional strategies, both directly and through digital media. JAPOSANG is expected to become a signature product of Buata Village, not only known locally but also marketed to wider regions and potentially recognized as a regional specialty souvenir.